Arc Vapour Deposition Of Iron Film During Magnetron Sputtering Of Ti Film: Effect Of Substrate’s Materials And Surface Roughness - Lau, Kok Tee; Zurianee, Lokman Loganathan; Roslan, Abd. Shukor (Electrochemical Science Group, 2015)
Arcing of non-target surface is the main contamination cause of sputtering process, which could be minimized through the effective control of the deposition parameters. However, there is an insufficient understanding of the arc vapour deposition’s role to the film contamination during magnetron sputtering process, particularly on different substrate’s materials and surface roughnesses. Thus, the current paper investigates the arc vapour deposition of ionized iron atom contaminants on the conductive and nonconductive substrates with different surface roughnesses during the magnetron sputter deposition process. The electric arcing occurred on substrate holder was triggered by the electric short-circuit between the supposedly electrically isolated substrate holder and adjacent metallic components. Energy dispersive X-ray spectroscopy and X-ray diffraction indicate that all the deposited films composed of iron (α-ferrite) as the dominant element, with Ti as the minor element. Scanning electron microscopy shows thicker iron films were deposited on the conductive aluminium and mild-steel substrates, in comparison to the film deposited on the nonconductive glass substrate. Field-emission scanning electron microscopy displayed columnar structure for the iron films. The variation in film thickness between the conductive and nonconductive substrates can be explained by the following mechanism: (i) stronger Coulombic attractions of the incoming ionized Fe atoms to the larger electric field generated by conductive substrate, and/or (ii) stronger Coulombic repulsion of the incoming ionized Fe atoms by the deposited Fe ions trapped on nonconductive substrate due to poor electrical grounding. Thus, substrate’s material and surface roughness are the determining factors controlling the deposition rate of ionized iron atoms onto the substrate during the arc vapour deposition process.